Disease Biomarkers of Giardiasis - Norhamizah Roshidi; Norsyahida Arifin (Journal of Parasitology Research)
Giardiasis is a common, treatable intestinal disease that adversely affects underprivileged communities living in unsanitary conditions. Giardiasis causes a wide spectrum of gastrointestinal diseases in those infected, ranging from subclinical disease that can manifest as irritable bowel syndrome with persistent abdominal symptoms. Importantly, giardiasis has been identified as a predictor of malnutrition among young children in rural areas and as a cause of waterborne mass epidemics endangering not only humans but also animals in a broad clinical, social, and economic spectrum. While the diagnosis of giardiasis is heavily dependent on the presence of cysts and/or trophozoites detected using microscopy, the intermittent cyst excretion, low infection intensity, and low sensitivity method m4akes fecal examination unrewarding, thus urging the need for an improved diagnostic method for giardiasis. Proteins are key compounds in biosynthesis, cells, tissues, and organ signaling, carrying important information related to biological and pathogenic processes, as well as pharmacological responses to therapeutic intervention, and are therefore important indicators for determining disease onset, progression, and drug treatment effectiveness. In connection with this, proteins could serve as promising biomarkers for antigen-antibody detection, as well as vaccine candidates. This article is aimed at providing a comprehensive overview of proteins, serological, molecular, inflammatory, volatile, and hormonal biomarkers associated with giardiasis and their potential for diagnostics and therapeutics.